The symbolic meaning of turquoise in Iranian culture - Zhetpisbayeva, K.B.; Zhubatova, B.N. (Journal of Oriental Studies, 2021)
This article is intended to determine the symbolic meaning of turquoise in Iranian culture with the help of extralinguistic materials. Today, gemstones are not just ordinary useful minerals, because they can become the main object of complex research as a living element of a particular culture. The lack of research on this topic in the field of Iranian studies, in turn, determines the relevance of the study. The research is interdisciplinary in nature, based on the linguocultural and etymological analysis, method of interpretation. The results of the study can be used by orientalists, specialists in Iranian studies and linguists in conducting linguocultural analysis. In the article, the authors reveal that the turquoise stone has a special place in Iranian culture, as well as the fact that this precious stone is valuable as a natural mineral, and its color is associated with Iranian archetypal beliefs. In addition, the role of turquoise stone in religious discourse and its widespread usage as medicine has enhanced the status of this stone. And the analysis of the appearance of the turquoise stone, which is used as a metaphor and simile in the literary texts of Persian poets, allows a deeper understanding of the Eastern poetry. Key words: Iran, culture, symbol, turquoise, blue, gemstones.